2015
DOI: 10.1098/rspb.2014.2519
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sister species identifies factors underpinning plastid compatibility in green sea slugs

Abstract: The only animal cells known that can maintain functional plastids (kleptoplasts) in their cytosol occur in the digestive gland epithelia of sacoglossan slugs. Only a few species of the many hundred known can profit from kleptoplasty during starvation long-term, but why is not understood. The two sister taxa Elysia cornigera and Elysia timida sequester plastids from the same algal species, but with a very different outcome: while E. cornigera usually dies within the first two weeks when deprived of food, E. tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 56 publications
(82 reference statements)
3
57
0
Order By: Relevance
“…Several ongoing plastid-acquisition types of endosymbiosis are observed in sacoglossan sea slugs such as Elysia chlorotica and E. timida [11,[35][36][37], and in the marine ciliate Mesodinium rubrum [38][39][40][41]. However, they are defective in their ability to maintain permanent endosymbiosis.…”
Section: Life Cycle Of Endosymbionts In P Bursaria Host Cell Analyzementioning
confidence: 99%
“…Several ongoing plastid-acquisition types of endosymbiosis are observed in sacoglossan sea slugs such as Elysia chlorotica and E. timida [11,[35][36][37], and in the marine ciliate Mesodinium rubrum [38][39][40][41]. However, they are defective in their ability to maintain permanent endosymbiosis.…”
Section: Life Cycle Of Endosymbionts In P Bursaria Host Cell Analyzementioning
confidence: 99%
“…About 2,000 proteins are needed to support photosynthesis in algae and plants, but only a fraction is encoded in the genome of plastids (Timmis et al, 2004) and none of the relevant genes were found in the slugs' genomes investigated so far (Wägele et al, 2011;Bhattacharya et al, 2013;de Vries et al, 2015;Han et al, 2015). This led to the search for alternative factors that enable kleptoplast longevity, and plastid photoprotection mechanisms came into focus (Jesus et al, 2010;Cruz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sacoglossan transcriptome reads were acquired in previous work by other groups 11,23 from 19 specimens of Elysia chlorotica, Elysia timida , and Elysia cornigera (Extended Data Table 3). We downloaded the reads from the NCBI Sequence Read Archive (SRA) and assembled them using IDBA-UD 44 .…”
Section: Methodsmentioning
confidence: 99%
“…We were unable to identify good candidate polypropionate synthases from the bacterial metagenomes, suggesting a possible origin in the animals or chloroplasts. We took advantage of recently released genomes and transcriptomes of three sacoglossans 11,2224 , Elysia chlorotica, E. timida , and E. cornigera , to test this hypothesis. E. chlorotica contains polypropionates ent -9,10-deoxytridachione and elysione 25 , while E. timida contains ent -9,10-deoxytridachione and several relatives (Fig.…”
Section: Mainmentioning
confidence: 99%